Korupsi dan Pengaruhnya Terhadap Investasi Asing Langsung di Negara – Negara Berkembang - Harly Clifford Jonas Salmon (LUTUR Law Journal, 2024)
According to the Big Indonesian Dictionary (KBBI), corruption is the misappropriation or attack of state funds (companies, organizations, foundations, and so on) for personal or other people's interests. Corruption is a complex and detrimental phenomenon that affects many aspects of life in developing countries, including foreign direct investment. Foreign direct investment has an important role in driving economic growth, creating jobs, and transferring technology in developing countries. However, corruption can be a serious obstacle to the attractiveness of such investments. Therefore, it is important to understand the effect of corruption on foreign direct investment in the context of developing countries. The purpose of this study is to analyze the effect of corruption on foreign direct investment in developing countries. The research method used is the normative method because in normative research it mainly uses library materials as a source of research data or also called (library research), the method used to collect data from various literature. Collection of legal materials through secondary legal materials then management and analysis of legal materials is described qualitatively. From the results of our research, corruption has a very negative effect on foreign direct investors or FDI in developing countries. This can prevent the entry of new foreign investors and affect the business continuity of existing companies. Investors usually choose countries with an open, fair and corruption-free business environment. Countries that wish to eradicate corruption, improve governance and increase legal certainty tend to be more attractive to foreign investors. Corruption also has negative impacts on developing countries such as uncertainties and risks for foreign investors, additional fees or bribes for foreign companies, and weak infrastructure for public services.